2018
DOI: 10.1002/adma.201707072
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Function Electrocatalytic and Macroporous Hollow‐Fiber Cathode for Converting Waste Streams to Valuable Resources Using Microbial Electrochemical Systems

Abstract: Dual-function electrocatalytic and macroporous hollow-fiber cathodes are recently proposed as promising advanced material for maximizing the conversion of waste streams such as wastewater and waste CO to valuable resources (e.g., clean freshwater, energy, value-added chemicals) in microbial electrochemical systems. The first part of this progress report reviews recent developments in this type of cathode architecture for the simultaneous recovery of clean freshwater and energy from wastewater. Critical insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(55 citation statements)
references
References 194 publications
2
53
0
Order By: Relevance
“…Various methods including electrocatalysis, photocatalysis, biocatalysis by cyanobacteria, green algae, and some autotrophic bacteria, and chemical transformation through organic reactions, have been proposed in the literature for the conversion of CO 2 into useful products. [1b,4,8] Of the different methods studied, electrochemical reduction of CO 2 to useful chemicals such as methane (CH 4 ), methanol (CH 3 OH), ethylene (C 2 H 4 ), ethanol (CH 3 CH 2 OH), formic acid (HCOOH), carbon monoxide (CO), etc., appears to be the most promising approach because: 1) the electrocatalytic process can be conducted in ambient conditions with highly controllable reaction step;[1b,9] 2) the products of electrochemical reduction can be adjusted by varying the reaction parameters; 3) the electrochemical reduction system can be employed for practical application; and 4) the electric power required to drive the system can be obtained from renewable energy sources such as solar or wind. [1b,4,9] The latter is attractive because it can solve one of the main issues in the proliferation and development of renewable energy, and that is intermittency, by providing an energy storage solution for intermittent renewable energy sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods including electrocatalysis, photocatalysis, biocatalysis by cyanobacteria, green algae, and some autotrophic bacteria, and chemical transformation through organic reactions, have been proposed in the literature for the conversion of CO 2 into useful products. [1b,4,8] Of the different methods studied, electrochemical reduction of CO 2 to useful chemicals such as methane (CH 4 ), methanol (CH 3 OH), ethylene (C 2 H 4 ), ethanol (CH 3 CH 2 OH), formic acid (HCOOH), carbon monoxide (CO), etc., appears to be the most promising approach because: 1) the electrocatalytic process can be conducted in ambient conditions with highly controllable reaction step;[1b,9] 2) the products of electrochemical reduction can be adjusted by varying the reaction parameters; 3) the electrochemical reduction system can be employed for practical application; and 4) the electric power required to drive the system can be obtained from renewable energy sources such as solar or wind. [1b,4,9] The latter is attractive because it can solve one of the main issues in the proliferation and development of renewable energy, and that is intermittency, by providing an energy storage solution for intermittent renewable energy sources.…”
Section: Introductionmentioning
confidence: 99%
“…[7a,c,13] For example, Nichols et al[7a] combined a biocompatible photo(electro)chemical HER catalyst with an autotrophic obligate anaerobic archaeon, Methanosarcina barkeri , that uses the in situ generated H 2 for CO 2 reduction to CH 4 . A new approach that has emerged in recent years is that of microbial electrosynthesis (MES), which relies on chemolithoautotrophic bacteria or archaea that can uptake electrons directly or indirectly (for example, as H 2 or formate) from the cathode of an electrochemical cell to catalyze the reduction of CO 2 into fuels or value‐added chemicals at low potentials . In this regard, MES acts as a hybrid biosystem where the biocompatible material component (cathode) catalyzes the HER to generate H 2 and the microbial component, which forms a biofilm on the cathode, uses these reducing equivalents to fix CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Zhang et.al confirmed that the low solubility of H 2 in water might cause energy losses . Recently, to facilitate the delivery of CO 2 into the biocathode, a Ni‐based electrically conductive, catalytic, and porous hollow‐fiber cathode was applied for reducing CO 2 to CH 4 . Also, a porous nickel hollow‐fiber cathode coated by carbon nanotubes was developed to promote the transport of CO 2 to S. ovata to improve the production rates .…”
Section: H2 Generation and Utilizationmentioning
confidence: 99%
“…Modifications of these cathodes such as improving the surface chemistry and the surface area have been increasingly explored to optimize MES systems. Recently, macroporous hollow‐fiber cathodes are recently proposed as promising advanced material for maximizing the conversion of CO 2 to valuable resources . Carbon cloth cathodes were modified with reduced graphene oxide functionalized with tetraethylene pentamine (rGO‐TEPA) to enhance the attachment of S. ovata and then form biofilms with unique spatial arrangement which resulting in acetate production rate 3.6‐fold higher than the controls .…”
Section: Microbial Electrosynthesismentioning
confidence: 99%
“…Recently, macroporous hollow-fiber cathodes are recently proposed as promising advanced material for maximizing the conversion of CO 2 to valuable resources. [66] Carbon cloth cathodes were modified with reduced graphene oxide functionalized with tetraethylene pentamine (rGO-TEPA) to enhance the attachment of S. ovata and then form biofilms with unique spatial arrangement which resulting in acetate production rate 3.6fold higher than the controls. [67] Besides, Bajracharya et al assembled a graphite felt and stainless steel as cathode in the MES driven by a mix culture with the maximum acetate production rate of 1.3 mM day À1 at À1.1 V vs. Ag/AgCl.…”
Section: Microbial Electrosynthesis For Co 2 Conversionmentioning
confidence: 99%